1990
DOI: 10.1210/endo-127-1-467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endocrine Manipulation on Anterior Pituitary Galanin in the Rat

Abstract: Galanin is widely distributed throughout the rat neural and endocrine system. The highest concentrations are found in the anterior pituitary, and it can influence classical pituitary hormone secretion. The effects of endocrine manipulation on pituitary galanin content, mRNA, and immunostaining have been investigated in the rat. In females, medical (39 +/- 4 fmol/gland), surgical (33 +/- 2), or combined (28 +/- 6) castration resulted in a highly significant decrease in galanin content (control, 223 +/- 14; P le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 30 publications
6
45
2
Order By: Relevance
“…GAL-LI was localized in the cytoplasm of the gonadotrophs and thyrotrophs in the anterior lobe. These findings are in contrast with the data on immunocytochemical studies in rats and humans [14][15][16][17]. Steel et al [14] have shown that GAL-LI is present mainly in lactotrophs, with a small number of somatotrophs and thyrotrophs appearing in normal and estrogen-treated female rats.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…GAL-LI was localized in the cytoplasm of the gonadotrophs and thyrotrophs in the anterior lobe. These findings are in contrast with the data on immunocytochemical studies in rats and humans [14][15][16][17]. Steel et al [14] have shown that GAL-LI is present mainly in lactotrophs, with a small number of somatotrophs and thyrotrophs appearing in normal and estrogen-treated female rats.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, GAL mRNA within the anterior lobe of rats has been demonstrated by in situ hybridization [15,16,18]. In the present study, we present our results on the identification of pituitary cell types in the male monkey exhibiting GAL-LI by means of an elution-restaining procedure.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Temporally linked with the appearance tion (40,41). Second, the anterior pituitary itself produces considerable quantities of galanin ( 42,43), making it difficult to of FOS and JUN, cellular levels of galanin mRNA in GnRH neurons are also increased, and anatomical comparisons suggest conceive how minute amount of galanin reaching the pituitary from the portal circulation could have a significant impact on that it is the identical population of GnRH neurons that expresses both FOS and galanin (8 ). There are elements on the 5∞ flanking pituitary function.…”
Section: Discussionmentioning
confidence: 99%
“…An RIA for total galanin content in WT (n ϭ 3) and GAL-tg (n ϭ 3) forebrain was conducted as previously described (36), with minor modifications. Galanin antiserum (diluted 1:80,000) was directed against rat galanin and showed a 35 and 15% crossreactivity with porcine and human galanin, respectively, and no crossreactivity with any other neuropeptides examined.…”
Section: Generation Of Galanin Transgenic Micementioning
confidence: 99%